A LINGUISTIC ANALYSIS OF UZBEK NATIONAL DISH NAMES IN ENGLISH AND RUSSIAN LITERARY WORKS - Zarina Rashidovna Bobojonova (Bright Mind Publishing, 2025)
This article investigates the linguistic representation of Uzbek national dish names in English and Russian literary works, focusing on the intersection of language, culture, and translation. Food terminology is closely tied to cultural identity and reflects unique national traditions. The study explores how Uzbek culinary terms such as plov, somsa, lag‘mon, and shurpa are integrated, translated, or adapted in English and Russian contexts. Drawing on the principles of linguoculturology, translation studies, and comparative lexicology, the paper analyzes semantic shifts, strategies of domestication and foreignization, and the cultural connotations of culinary realia. The findings demonstrate that Russian literature, due to its long-standing cultural contact with Uzbekistan, tends to naturalize these terms, whereas English literature often treats them as exotic items requiring explanation.
Keywords: Uzbek cuisine terminology; linguistic analysis; culinary realia; English and Russian literary discourse; cultural transfer; domestication and foreignization; translation strategies; linguacultural.